92PDetection of PIK3CA mutation by circulating DNA during chemotherapy: A tool to identify hard-to-treat metastatic breast cancers. (7th November 2019) - Mosele, F; Lusque, A; Tran Dien, A; Droin, N; Le Tourneau, C; Sablin, M P; Lacroix, L; Miran, I; Jovelet, C; Bieche, I; Soria, J-C; Bertucci, F; et al.
Abstract: Background: α-selective PI3K inhibitors improve PFS in patients with HR+/Her2- metastatic breast cancer (mBC) and PIK3CA mutation. Recent studies have reported that a subset of patients with PIK3CA-mutated HR+/Her2- mBC are chemoresistant. Therefore, there is a need to identify these patients in order to propose them alternative therapies, including PI3K inhibitors. Methods: 44 patients from SAFIR02 trial (NCT02299999), with mBC and PIK3CA mutation, detected by NGS on metastatic samples, were analyzed. We studied the prognostic value of the level of cell-free circulating PIK3CA mutations, determined by NGS and digital PCR, in plasma samples during chemotherapy. They were obtained after one cycle of chemotherapy in 66% of patients, two cycles in 20% of patients, and three cycles in 14% of patients. Results: PIK3CA mutations were detectable on circulating DNA in 26 of the 44 patients (59%) analyzed. 38 (88%) tumors were HR+/Her2- and there were only 5 (12%) TNBC. The most frequent metastatic sites were liver (79%), bone (75%), and lung (23%). 89% of patients received first-line of chemotherapy at the time of screening. The level of PIK3CA mutations detected in plasma during chemotherapy was associated with a poor outcome (continuous variable, Hazard Ratio for Overall Survival (OS): 1.03, 95% CI [1.01-1.05], p = 0.007). The median OS for patients with a minor allele frequency (MAF) ≥ median was 14 months vs 26 for patients with a MAF < median (p < 0.0001), and 6 months vs 25.6 for patients with a MAF ≥ or < 5 respectively (p < 0.0001). Conclusions: Patients with persistent levels of cell-free circulating PIK3CA mutations during chemotherapy present a poor outcome. Pending a validation study, these patients could be eligible to innovative therapy as soon as 1 st line chemotherapy. Legal entity responsible for the study: The authors. Funding: Fondation ARC Pour La Recherche Sur Le Cancer, Breast Cancer Research Foundation, Operation Parrain Chercheurs and Transcan. Disclosure: C. Le Tourneau: Advisory / Consultancy: Amgen; Advisory / Consultancy: GSK; Advisory / Consultancy: AstraZeneca; Advisory / Consultancy: Nanobiotix; Advisory / Consultancy: MSD; Advisory / Consultancy: BMS; Advisory / Consultancy: Merck Serono; Advisory / Consultancy: Roche. M.P. Sablin: Speaker Bureau / Expert testimony: Servier. J-C. Soria: Honoraria (institution), full time employer since September 2017: AstraZeneca; Advisory / Consultancy: Astex; Advisory / Consultancy: Clovis; Advisory / Consultancy: GSK; Advisory / Consultancy: GamaMabs; Advisory / Consultancy: Lilly; Advisory / Consultancy: MSD; Advisory / Consultancy: Mission Therapeutics; Advisory / Consultancy: Merus; Advisory / Consultancy: Pfizer; Advisory / Consultancy: PharmaMar; Advisory / Consultancy: Pierre Fabre; Advisory / Consultancy: Roche/Genentech; Advisory / Consultancy: Sanofi; Advisory / Consultancy: Servier; Advisory / Consultancy: Takeda; Advisory / Consultancy: Symphogen; Honoraria (self), Shareholder: AstraZeneca/Genentech. M. Campone: Honoraria (institution): Novartis. T. Bachelot: Honoraria (self), Research grant / Funding (self), Non-financial support: Novartis; Honoraria (self), Research grant / Funding (self), Non-financial support: AstraZeneca; Honoraria (self), Research grant / Funding (self), Non-financial support: Pfizer; Honoraria (self): Seattle Genetics. F. André: Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (self): Novartis; Research grant / Funding (self), Outside the work: Pfizer, Lilly, Sanofi, Roche, AstraZeneca, Daiichi. All other authors have declared no conflicts of interest.